Proceedings of XTH Quark Confinement and the Hadron Spectrum — PoS(Confinement X) 2013
DOI: 10.22323/1.171.0024
|View full text |Cite
|
Sign up to set email alerts
|

Round Table: Resolving Physics BSM at Low Energies

Abstract: Low-energy precision experiments can reveal physics beyond the standard model through either the observation of the violation of expected fundamental symmetries or an observed deviation from a precision calculation. We offer an overview of the possibilities, thereby illuminating the subfield's essential challenges and themes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This agrees well with the result obtained by Ebel and Feldman [2]. However, in addition to the result obtained by Ebel and Feldman [2] we, following [48][49][50][51][52] (see also [3,16,18,19,47]), have taken the contributions of the phenomenological vector coupling constants C V and CV in the linear approximation, i.e. C V = 1 + δC V and CV = −1 + δ CV , where we have used the notations of [3,16,18,19,47].…”
Section: Contributions Of Interactions Beyond the Standard Model And ...supporting
confidence: 89%
“…This agrees well with the result obtained by Ebel and Feldman [2]. However, in addition to the result obtained by Ebel and Feldman [2] we, following [48][49][50][51][52] (see also [3,16,18,19,47]), have taken the contributions of the phenomenological vector coupling constants C V and CV in the linear approximation, i.e. C V = 1 + δC V and CV = −1 + δ CV , where we have used the notations of [3,16,18,19,47].…”
Section: Contributions Of Interactions Beyond the Standard Model And ...supporting
confidence: 89%
“…Direct searches for new particles and interactions at colliders certainly involve precision measurements and in the search for new physics in low-energy processes. There is a large array of possible observables to consider; we refer the reader to a brief, recent overview [1237], as well as to a dedicated suite of reviews [1238][1239][1240][1241][1242][1243][1244][1245]. In this chapter we describe the theoretical framework in which such experiments can be analyzed before delving more deeply into examples which illustrate the themes we have described.…”
Section: Introductionmentioning
confidence: 99%
“…In addition we have calculated the contributions of interactions beyond the SM, expressed in terms of i) the phenomenological coupling constants of the effective phenomenological interactions proposed by Jackson et al [25], and ii) the phenomenological coupling constants of the second class currents, measuring the strength of G-odd correlations [66,73,74] (see also [30,31]). We have found that in the linear approximation for the phenomenological vector, axial-vector, scalar and tensor coupling constants [18][19][20][21][22] (see also [28,29,31]) the contribution of interactions beyond the SM, defined by the effective Lagrangian Eq. (25), is equal to zero, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…At the replacement C V = − CV = 1, C A = − CA = g A and C S = CS = C P = CP = C T = CT = 0 the factor ξ reduces to ξ = 2(1 + 3g 2 A ). In the linear approximation for the phenomenological vector and axial-vector coupling constants C V = 1 + δC V , CV = −1 + δ CV , C A = g A + δC A and CA = −g A + δ CA the contributions of the vector and axial-vector phenomenological coupling constants can absorbed by renormalization of the axial coupling constant g A and the Cabibbo-Kobayashi-Maskawa (CKM) matrix element V ud (it is included into G V ) [18][19][20][21][22] (see also [28,29,31]). Thus, in the linear approximation for the phenomenological vector, axial-vector, scalar and tensor coupling constants [18][19][20][21][22] (see also [28,29,31]) the contribution of interactions beyond the SM, defined by the effective Lagrangian Eq.…”
Section: Contributions Of Interactions Beyond the Standard Model [25]mentioning
confidence: 99%
See 1 more Smart Citation